Introduction to the Symposium on Critical International Law and Technology - Fleur Johns; Gregor Noll (AJIL Unbound, 2023)
Scholarship concerned with international law, technology, and computation has been burgeoning since the mid-to-late twentieth century. Over the past decade, it has taken shape as a discernible sub-field of international legal scholarship. An International Law and Technology Interest Group was created within the American Society of International Law in 2013, for instance. By 2021, international law and technology was already considered ripe for “rethinking.” Some of this work has been solutionist, aimed at generating order-restoring answers to the “upset[s]” caused by technological change. Some of it has been constitutionalizing, canvassing prospects for “a transformative constitutionalism for the digital human condition.” Much of the scholarship has sought to give humanist (or post-humanist) pause to the ever-increasing pace of technological change.